Tasks, Skills, and Institutions The Changing Nature of Work and Inequality - Gradín, Carlos; Lewandowski, Piotr; Schotte, Simone; Sen, Kunal (WIDER Studies in Development Economics, 2023)
This book provides a unique, comparative assessment on how the nature of work is changing in 11 major developing countries, and the role that these changes play in shaping earnings inequality in these societies. It provides a nuanced and context-sensitive developing-country perspective with an in-depth assessment of national trends in earnings inequality, which are assessed against changes in the supply of higher skilled workers and education premia, on the one hand, and changes in the occupational structure and the remuneration of tasks, on the other, while being mindful of broader macroeconomic trends and institutional developments. We start showing that the common assumption that occupations are identical around the world tends to lead to an overestimation of the non-routine task content of jobs in developing and emerging economies. Then, we use country-specific measures of routine-task intensity, along with the standard O*NET measures, and other innovative ways to push the boundaries of existing research and make the most of the limited information that is available in each of the countries under study. We show that the large changes in the composition of workers by education and job routine-task intensity, which developing countries exhibited in the 2000s and 2010s, generally contributed to higher inequality, ceteris paribus. We also find evidence of job polarization or widening of earnings inequality driven by the evolution of routine intensity of jobs in several cases. However, changes in the education premium, along institutional factors, seem to explain inequality trends to a larger extent.